Administrative empowerment among females’ leaders in secondary schools in Hafr Al-Batin and its social, cultural and environmental challenges - Alanazi, Mona Mutlaq (Journal of Educational and Psychological Sciences, 2023)
Although women make up half the world's population and more than 40 percent of the global workforce, the issue of empowering women to lead in educational institutions remains highly controversial. The concept of women's empowerment emerged in the eighties and nineties of the last century as a kind of recognition of the inequality between women and men. Empowerment of women was dealt with as an institutional concept that might help bring about a change in the skills of female educational leaders in Saudi secondary schools, but in fact there was a clear scarcity in the literature that and Arab studies that were analyzed in the study of the concept of administrative empowerment and the obstacles that female principals may face. Saudi women in secondary schools in Hafr Al-Batin to implement it.Using the qualitative interpretivist research method, this study attempted to survey the opinions of a selected group of secondary school principals to investigate their understanding and knowledge of the term administrative empowerment, and then to identify the social, religious, and economic obstacles that may prevent principals from administrative empowerment.Through conducting and analysing ten face-to face- semi-strcutured interviews, it was concluded that the understanding of the concept of administrative empowerment was linked by a few leaders to follow laws and regulations. Indeed, small group of the participant confirmed that educational bureaucratic institutions often do not allow the application of the concept of administrative empowerment, since the application of the concept requires creativity and departure from the norm. Another group of female’s leaders found it difficult to define the meaning of administrative empowerment, and most of them linked it to religion and masculinity in society.The study demonstrated the inability of some female’s leaders to describe the concept or comment on it. Therefore, the research concluded that the training provided to secondary school principals should be reconsidered, and it was pointed out the need to do more qualitative research that goes into the depth of analysing the religious, cultural, and social factors that impede women of administrative empowerment in other contexts.
Keywords: Leaders; High school; Empowerment; qualitative research; Social Obstacles